Role of omega-3 unsaturated acids in prevention and treatment of different diseases (part 1) - E. Yu. Plotnikova; M. N. Sinkova; L. K. Isakov (Лечащий Врач)
Currently, one of the most discussed issue in medicine is importance of omega-3 fatty acids for human body. There are several types of omega fatty acids: omega-9, omega-6 and omega-3 polyunsaturated lipids. There are clear distinctions among them, both by chemical structure, and by influence on human body. It is the excess of omega-6 that leads to sluggish inflammatory process in the vascular walls, joints, heart and brain. The article covers action mechanisms and effects of omega-3 fatty acids in different diseases. The questions of correlation of omega-6 and omega-3 polyunsaturated fatty acids in nutrition are considered, as well as norms of consuming omega-3 fatty acids in prevention and treatment of different diseases.